Засновник Української радикальної партії – Северин Данилович у спогадах дочки Євгенії - Борчук, С.; Плекан, Ю. (Краєзнавство, 2020)
У дослідженні вперше публікуються спогади Євгенії Северинівни Данилович про свого батька Северина Теофіловича Даниловича – відомого західноукраїнського громадсько – політичного діяча, науковця, правника (кінець ХІХ – перша половина ХХ ст.). Severyn Teofilovych Danylovych is one of the founders of Rusko and Ukrainian Redical Party and its magazines «Svit», «Narod», «Khliborob», «Gromadskyi Golos». He was editor in Chief and author of different articles. He had great influence on the political views of Vasyl Stefanyk, Les Martovych, Levko Bachynskyi. After graduation of Lviv University, Severyn moved out to Kolomyia town where he opened Law Firm expanding public activity. In 1890 he merried to Anna Gamorak, a daughter of a Greek Catholic priest and Galicia seim deputy, Kyrylo Gamorak who lived in Stetsiv village, Snyatyn district, Ivano-Frankivsk region. Lawyer Severyn Danylovych continued his science and political activity so he had to move to different county towns of East Galicia. His wife and daughters had to «travel» with him sharing his interesting and risky life. In the article you can find memories of 1982 of his daughter Yevgenia.